Trade in Intermediate Producer Services under Imperfect Competition - Aidan Islyami (FIW - Research Centre International Economics, 2009)
In this paper a stylized CGE model is constructed to study the impact of liberalization of barriers for foreign providers of intermediate producer services under imperfect competition on the welfare, the downstream industry output, the prices of the factors of production and the pattern of trade. An attempt is made at incorporating oligopoly market structure into the services sector within general equilibrium model. Consequently, a model with firms making output conjectures about domestic and foreign rivals is adopted. The case of a small developing country with less efficient services sector relative to the foreign firms is assumed. In this framework, interaction and the relative significance of mechanisms resulting from the love of variety, anti and pro competitive and the efficiency effects on the outcomes of the services liberalization is analyzed. It is found that the liberalization services trade might be negative in terms of welfare and downstream industry expansion even if the profits of the foreign firms are not shifted abroad. This represents the evidence of dominant anticompetitive effect. It is therefore important to take into consideration the underlying market structure while liberalizing services trade.
Keywords: F12; F23; C68; 330; Trade in services; CGE modeling; Imperfect competition